Keeping up with the therapeutic advances in schizophrenia: a review of novel and emerging pharmacological entities - Krogmann, Amanda; Peters, Luisa; von Hardenberg, Laura; Bödeker, Katja; Nöhles, Viktor B.; Correll, Christoph U. (CNS spectrums, 2019)
Schizophrenia remains one of the most severe medical diseases. Current dopamine modulating first-generation and second-generation antipsychotics target mainly positive symptoms, but not/inadequately negative and cognitive symptoms. Additional challenges include non-adherence and adverse effects, especially cardiometabolic dysregulation. This review evaluates new/emerging pharmacological treatments for schizophrenia. Therapies targeting total symptoms include cannabidiol, D3 antagonist/5-HT1A partial agonist F17464, lumateperone (ITI-007), phosphodiesterase 10A (PDE10A) inhibitors MK-8189 and TAK-063, sodium nitroprusside, and trace amine-associated receptor-1 (TAAR1) agonist RO5263397 and SEP-363856. Treatments targeting negative symptoms include the PDE10A inhibitor LuAF-11167, 5-HT2A inverse agonist pimavanserin, sigma-2/5-HT2A antagonist roluperidone (MIN-101), and d-amino acid oxidase (DAAO) inhibitor TAK-831. Agents targeting primarily cognitive dysfunction are the glycine transporter-1 inhibitor BI-425809 and cannabidiol. Therapies targeting residual positive symptoms/treatment-resistant schizophrenia include pimavanserin, dopamine D1/D2 antagonist LuAF-35700, and DAAO inhibitor sodium benzoate. Two new long-acting injectable antipsychotic formulations, Aripiprazole Lauroxil NanoCrystal® and the first subcutaneous injectable LAI Perseris (RBP-7000), were recently approved by U.S. Food and Drug Administration, and positive results were announced for Risperidone ISM®, each achieving therapeutic levels within 24 hours, without need for initial oral cotreatment/loading injection-strategies. Paliperidone palmitate 6-monthly intramuscularly injectable and Risperidone subcutaneously injectable TV46000 are currently under investigation. Finally, the samidorphan+olanzapine combination targets reduced weight gain liability, while maintaining olanzapine’s efficacy. Most of these trial programs are still ongoing or have yielded mixed or even negative results. Thus, additional mechanisms of action and agents require study to improve schizophrenia outcomes for total/positive symptoms with reduced adverse effects, but also cognitive symptoms, negative symptoms, and treatment resistance, the areas of greatest need in schizophrenia currently.